2015
DOI: 10.1186/s12918-015-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron acquisition and oxidative stress response in aspergillus fumigatus

Abstract: BackgroundAspergillus fumigatus is a ubiquitous airborne fungal pathogen that presents a life-threatening health risk to individuals with weakened immune systems. A. fumigatus pathogenicity depends on its ability to acquire iron from the host and to resist host-generated oxidative stress. Gaining a deeper understanding of the molecular mechanisms governing A. fumigatus iron acquisition and oxidative stress response may ultimately help to improve the diagnosis and treatment of invasive aspergillus infections.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 78 publications
(146 reference statements)
0
26
1
Order By: Relevance
“…Interestingly, iron was recently shown to be essential to oxidative stress response in A. fumigatus . 28 In this study, although there was no significant association between catalase activity and AMB susceptibility at the population level, all tested strains produced abundant catalase. It is entirely possible that once the catalase activity reached a certain level, there was little selective advantage to further increase its activity in nature.…”
Section: Discussioncontrasting
confidence: 53%
“…Interestingly, iron was recently shown to be essential to oxidative stress response in A. fumigatus . 28 In this study, although there was no significant association between catalase activity and AMB susceptibility at the population level, all tested strains produced abundant catalase. It is entirely possible that once the catalase activity reached a certain level, there was little selective advantage to further increase its activity in nature.…”
Section: Discussioncontrasting
confidence: 53%
“…The importance of high affinity iron acquisition strategies to the pathogenicity of A. fumigatus has been well defined [5,6,68]. Strict regulation of these strategies represents an integral mechanism of cellular homeostatic maintenance to avoid generation of deleterious ROS [70]. Proteomic analyses carried out herein indicate significant and functional microsomal proteome remodelling under iron limitation.…”
Section: Tablementioning
confidence: 81%
“…Iron metabolism is interconnected with the regulatory production of ROS. In A. fumigatus , Brandon et al predicted blocking siderophore-mediated iron uptake reduces resistance to oxidative stress by constructing a Boolean network model (Brandon et al, 2015 ). Remarkably, Chen et al also demonstrated in the citrus fungal pathogen Alternaria alternata that siderophore-mediated iron acquisition has profound effects on ROS detoxification by regulating the NADPH oxidase, the redox activating yes- associated protein 1 regulator, and the high-osmolarity glycerol 1 mitogen-activated protein kinase (Chen et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%